The National Information Exchange Model and making data relevant - Wormeli, Paul (International Journal of Population Data Science, 2018)
The National Information Exchange Model (NIEM) has been widely adopted as a basis for creating standards that foster information exchanges across disparate disciplines in justice, health, human services and other fields. NIEM can be a driver for transforming legacy data into meaningful cross-disciplinary exchanges that can support advanced analysis of impacts of programs and strategies in improving government services of all categories. This presentation will review the basic NIEM principles in terms of how they can enable more meaningful results as administrative data is applied to research on the efficacy of government services across organizations and disciplines.